Digital technologies: Civilian vs. military trajectories - Dario Guarascio; Mario Pianta (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2025)
The article examines the evolution of the current technological paradigm, based on digital technologies, considering the interaction between civilian and military trajectories, with a focus on the US case. Building on an original political economy framework, the activities of corporations and the industrial and technology policies of the US government are examined. The evolution of digital technologies and the rise of major US corporations - Alphabet, Amazon, Apple, Meta, Microsoft - is investigated, showing that their platform business model is characterised by monopoly power, management of Big Data and major capabilities of control, surveillance and targeting. A civilian trajectory - with large commercial markets and a novel reach in several areas of social activities - has dominated the rise of digital technologies. Its key characteristics, however, have become of major interest for military priorities. The analysis of recent US industrial and technology policies for the military shows that they have expanded the involvement of US digital corporations in arms and security programmes, developed large defense R&D projects in digital areas, and shaped a new convergence between civilian and military trajectories. The outcome we are facing is therefore the emergence of a digital-military-industrial complex - a major and problematic novelty in a digital age that had grown out of a civilian trajectory.
Keywords: O30; O33; 038; 330; digital technologies; technological trajectories; military programs